Aquatech secures ZLD project for Chinese coal-to-liquids plant. Issue 10 (October 2015) - Unknown
Abstract : US water purification technology company Aquatech is to provide a water treatment facility that includes a Zero Liquid Discharge (ZLD) plant for a coal to liquid fuels conversion project being developed by China's Shenhua Ningxia Coal Industry Co Ltd.